International Labor Migration and Its Transformative Effects on Political Landscapes Across Central Asian Nations - Egor V. Fomin; Albert A. Averyanov (RUDN Journal of Political Science, 2025)
In today’s context of global geopolitical transformation, competition for influence in Central Asia has intensified, particularly regarding the region’s labor resources. Currently, approximately 70 % of labor migration flows from Central Asian nations head towards the Russian Federation, while an overwhelming 90 % of financial remittances back home originate from Russia. Additionally, Russia plays a significant role through numerous investment initiatives across the region. The primary objective of this research is to explore the interplay between the economic and political ramifications of international migration patterns involving Central Asian states and the Russian Federation. Remittances sent by migrant workers to their homelands, along with Russian investments within these regions, serve as more than mere forms of “social security.” They significantly elevate overall standards of living, alleviate poverty levels, and importantly, bolster political stability among Central Asian nations situated along Russia’s southern periphery. However, emerging trends indicate shifts in traditional migration routes. New hubs attracting labor migrants include countries such as China, Turkey, Israel, Iran, Kazakhstan, South Korea, and others. This evolving landscape compels the Russian Federation into engaging in what can be described as a friendly yet competitive race for regional influence-even with some of its closest allies. This study concludes that any reduction in migratory activities, decreased inflows of remittance funds, or diminished organic inclination toward closer ties among migrants would result in both increased political volatility within Central Asia and weakened Russian leverage over the area.